"Edible Beauty": The Evolution of Environmentally Friendly Cosmetics and Packaging - Irene Dini (MDPI AG, 2024)
The cosmetics industry plays a significant role in the global economy and consumer lifestyles. Its dynamic and adaptable characteristics make it a key player worldwide. The cosmetics industry generates enormous profits globally, injecting billions of dollars into the world's economy each year. The industry's marketing efforts, product launches, and trends influence consumer behavior and perceptions of beauty, contributing to cultural dialogues and societal norms. This study, conducted with a rigorous bibliometric and systematic literature review, offers a comprehensive overview of recent progress in edible cosmetics. The "skincare you can eat" is an innovative branch of cosmetics that employs food co-products and by-products to create edible skincare and hair products and edible packaging materials to advance human well-being and sustainability while honoring the ecological boundaries of our planet. Nutrients and antioxidants derived from organic waste are used in cosmetics and packaging. Some doubts remain about the capacity of edible packaging to be attractive to consumers and offer a reasonable shelf life for cosmetics, and also about safety. It is desirable for the authorities to guarantee consumer health through carefully regulating labeling requirements and good manufacturing practices for cosmetics and edible packaging.